2021
DOI: 10.2217/fon-2020-1093
|View full text |Cite
|
Sign up to set email alerts
|

Luspatercept in the Treatment of Lower-Risk Myelodysplastic Syndromes

Abstract: Transforming growth factor beta (TGF-β) signaling pathway is key to hematopoiesis regulation. Increased activation of this pathway contributes to ineffective terminal erythroid differentiation in myelodysplastic syndromes (MDS). Luspatercept is a novel fusion protein that traps TGF-β ligands preventing them from binding to Type II TGF-β receptors, thereby decreasing phosphorylated SMAD2/3 resulting in the downstream effect of promoting erythropoiesis. Seminal clinical trials using luspatercept, PACE-MD and MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Lenalidomide is approved for a small subset of MDS patients with chromosome 5q deletion 9 . In April 2020, luspatercept was approved by the US Food and Drug Administration for patients with very low to intermediate (Int) risk MDS 11 . AZA and decitabine have demonstrated improved response rates and prolonged time to AML transformation and survival compared to conventional care in randomized phase 3 trials, 12‐14 and both are indicated in higher‐risk patients, although decitabine is not approved in Japan 15,16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lenalidomide is approved for a small subset of MDS patients with chromosome 5q deletion 9 . In April 2020, luspatercept was approved by the US Food and Drug Administration for patients with very low to intermediate (Int) risk MDS 11 . AZA and decitabine have demonstrated improved response rates and prolonged time to AML transformation and survival compared to conventional care in randomized phase 3 trials, 12‐14 and both are indicated in higher‐risk patients, although decitabine is not approved in Japan 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“… 9 In April 2020, luspatercept was approved by the US Food and Drug Administration for patients with very low to intermediate (Int) risk MDS. 11 AZA and decitabine have demonstrated improved response rates and prolonged time to AML transformation and survival compared to conventional care in randomized phase 3 trials, 12 , 13 , 14 and both are indicated in higher‐risk patients, although decitabine is not approved in Japan. 15 , 16 Approximately 40% of patients fail to respond to HMA, 17 and most responders experience disease relapse within 2 years.…”
Section: Introductionmentioning
confidence: 99%